2011
DOI: 10.1007/s10616-011-9363-8
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effects of 6-o-palmitoyl-ascorbate combined with a capacitive-resistive electric transfer hyperthermic apparatus as compared with ascorbate in relation to ascorbyl radical generation

Abstract: The aim of the present study is to determine the anti-proliferative activity of 6-o-palmitoyl-L-ascorbic acid (Asc6Palm) that is a lipophilic derivative of L-ascorbic acid (Asc), on human tongue squamous carcinoma HSC-4 cells by combined use of hyperthermia in comparison to Asc. Asc6Palm or Asc were administered to HSC-4 cells for 1 h, to which hyperthermia at 42°C was applied for initial 15 min. After further 1-72 h incubation at 37°C, cell proliferation was determined with Crystal Violet staining. Ascorbyl r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Pilot trials on patients with glioblastoma multiforme have reported that CRET treatment can reduce peritumoral edema and intratumoral vascularization, and induce extensive necrosis in the tumor core and significant tumor growth reduction, without affecting the surrounding healthy brain tissue (9). More recently, Kato et al (22) have shown that CRET treatment administered at thermal doses can significantly potentiate the anticancer effect of 6-O-palmitoyl-ascorbate on human tongue squamous carcinoma cells. Moreover, recent experimental studies by our group have shown that in vitro stimulation with subthermal doses of 0.57 MHz, CRET electric currents, induces partial cytostasis in the human hepatocarcinoma cell line HepG2 (16).…”
Section: Discussionmentioning
confidence: 99%
“…Pilot trials on patients with glioblastoma multiforme have reported that CRET treatment can reduce peritumoral edema and intratumoral vascularization, and induce extensive necrosis in the tumor core and significant tumor growth reduction, without affecting the surrounding healthy brain tissue (9). More recently, Kato et al (22) have shown that CRET treatment administered at thermal doses can significantly potentiate the anticancer effect of 6-O-palmitoyl-ascorbate on human tongue squamous carcinoma cells. Moreover, recent experimental studies by our group have shown that in vitro stimulation with subthermal doses of 0.57 MHz, CRET electric currents, induces partial cytostasis in the human hepatocarcinoma cell line HepG2 (16).…”
Section: Discussionmentioning
confidence: 99%
“…In what concerns to CRET specifically, it has been shown to potentiate the action of antitumor agents on the human tongue squamous carcinoma HSC-4 [13]. Also, recent experimental results indicate that CRET effectiveness in cancer treatment may be enhanced by taking advantage of the ability of the radiofrequency current to heat metal nanoparticles embedded in the tumoral tissue [14].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary tests of CRet system on cancer patients also showed consistent signs of slowing down the growth of the tumor tissues without adverse effects in the surrounding healthy tissues [20,21]. Additonally, previous studies have shown that CRet treatment induces cytostatic effects in the human hepatocarcinoma HepG2 [16,17,19], cytotoxic effects in NB69 human neuroblastoma cells [18] and significantly potentiate anticancer effect of 6-O-palmitoyl-ascorbate on human tongue squamous carcinoma HSC-4 [22].…”
Section: Methodsmentioning
confidence: 73%
“…It has been established that H 2 O 2 is involved in the redox control of several physiologic processes, including cell proliferation and apoptosis [32,33]. Furthermore, we previously reported that combined treatment with AsA and CRet increased ascorbate radical formation in HSC-4 cells [22]. Therefore, these results suggest that both H 2 O 2 and ascorbate radical generation are related to the effects of combined treatment with AsA and CRet through cell growth suppression because of G2/M arrest and apoptosis induction (see Fig.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation